Palestine LTD. : neoliberalism and nationalism in the occupied territory - Haddad, Toufic; London Middle East Institute (London : I.B. Taurus & Co. Ltd, 2016)
This book explores how neoliberal frameworks have shaped and informed the common understandings of international, Israeli, and Palestinian interactions throughout the Oslo peace process.
Neoliberal approaches to conflict resolution and statebuilding -- Getting to 'peace': survey of historical, political and economic factors leading to the Oslo Peace Process -- Modeling a resolution -- The voyage: neoliberal peacebuilidng in practice 1993-2000 -- The enforcer: structural determinants of Palestinian political economy: the Israeli contribution -- The guesstimate: structural determinants of Palestinian political economy: international aid contributions -- Palestinian political actors negotiate neoliberal peacebuilding -- Rents, rent-seeking and the political settlement of the Oslo years -- Reform and statebuilding -- 'Fayyadism' -- Incentivinzing de-development.
Includes bibliographical references (pages 294-324) and index.
Keywords: Arab-Israeli conflict; Nationalism -- Palestine; Neoliberalism -- Palestine; Palestine -- Politics and government -- 1948-; Palestine -- Economic conditions